Powerful red-green-blue laser source pumped with a mode-locked thin disk laser - Brunner, Felix; Innerhofer, Edith; Marchese, Sergio V; Südmeyer, Thomas; Paschotta, Rüdiger; Usami, Takeshi; Ito, Hiromasa; Kurimura, Sunao; Kitamura, Kenji; Arisholm, Gunnar; Keller, Ursula (Optics letters, 2004)
We present a red-green-blue laser source with average powers of 8 W in the red, 23 W in the green, and 10.1 W in the blue. The entire pump power for the nonlinear conversion stages is provided by a single laser oscillator without any amplifier stages. Our system does not require any synchronized cavities, and all nonlinear crystals except one are critically phase matched at room temperature.